2022
DOI: 10.3390/su14095178
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Land Resource Carrying Capacity in 35 Major Cities in China

Abstract: With the rapid development of urbanization, it is necessary to understand the evolution of land resource carrying capacity (LRCC), so as to avoid irreversible damage to the land resources system in a specific region. Therefore, this paper aims to study the evolution of LRCC by four carrying status intervals of land resources. LRCC based on an evolutionary perspective can help the government manage land resources dynamically and rationally. This study defines LRCC from a carrier–load perspective and considers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This coincides with existing research outcomes [17][18][19]31]. This study refines the LCC model found in the literature [60][61][62] by incorporating food nutrition into the evaluation system. One of the findings of this research is that the LCC in China maintained a continuous surplus from 1990 to 2020, but is beginning to have a declining trend.…”
Section: Innovations and Contributionssupporting
confidence: 88%
“…This coincides with existing research outcomes [17][18][19]31]. This study refines the LCC model found in the literature [60][61][62] by incorporating food nutrition into the evaluation system. One of the findings of this research is that the LCC in China maintained a continuous surplus from 1990 to 2020, but is beginning to have a declining trend.…”
Section: Innovations and Contributionssupporting
confidence: 88%
“…In addition, official data also have the advantages of comparability, which facilitate cross-regional and comparative temporal analysis. Many previous studies have utilized official data as the foundation for their research, so this study also chooses to use official statistical data as the primary source of data [22,66]. The study uses panel data from 2000 to 2020 for the 13 MGPAs in China.…”
Section: Data Sourcementioning
confidence: 99%
“…Since the LRCC system is complex, it is difficult to directly determine the classification of the LRCC scores. Therefore, with reference to Luo et al (2022) [22], the LRCC scores were classified into five categories by calculating the average quintiles of the LRCC scores (Q 1 -Q 4 ) of the 13 provinces in the MGPAs in a certain year, as shown in Figure 2. Provinces with LRCC scores lower than or equal to the first quintile (Q 1 ) are considered to be great surplus provinces, indicating that their socioeconomic development is substantially below the carrying capacity of land resources.…”
Section: Determination Of Lrcc Score Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Development requires continuous acquisition of resources, and land is the carrier and body of those resources (Luo et al, 2022). However, land's scarcity and non-renewability can lead to intensifying conflicts between land functions.…”
Section: Introductionmentioning
confidence: 99%